Baduy Proverb Lojor Teu Beunang Dipotong, Pondok Teu Beunang Disambung, Gede Teu Beunang Dicokot, Leutik Teu Beunang Ditambah: Semantics View - Nehe, Berita Mambarasi (JEDLISH : Journal Of Education and English Language Teaching, 2024)
This research aims to understand the semantics of the Baduy proverb "Lojor Teu Beunang Dipotong, Pondok Teu Beunang Disambung, Gede Teu Beunang Dicokot, Leutik Teu Beunang Ditambah" and gain insights into the proverbial wisdom of the Baduy community. In this study, we present the background of Baduy culture, describe the research objectives, explain the research methodology, present the research findings, and draw relevant conclusions. The background of this research reflects the importance of preserving the integrity and culture of the nation, including the preservation of the Baduy community's culture. The Baduy community is known for their strict adherence to traditions and their strong system of beliefs and norms. Baduy proverbs are an integral part of their cultural identity and serve as moral and social guidelines in their daily lives. The objective of this research is to understand the semantic meaning of the Baduy proverb and explore the wisdom embedded in it. The research methodology employed is semantic analysis, which involves dissecting the meanings of words and phrases in the proverb while considering the cultural context surrounding it. The research findings indicate that the Baduy proverb "Lojor Teu Beunang Dipotong, Pondok Teu Beunang Disambung, Gede Teu Beunang Dicokot, Leutik Teu Beunang Ditambah" reflects values such as justice, simplicity, and wisdom in managing daily life. The proverb emphasizes the importance of maintaining integrity, preserving unity, respecting hierarchy, and appreciating small things. Based on these findings, the conclusion of this research is that the wisdom of Baduy proverbs holds significant value in preserving culture and tradition. As the future generation, we are tasked with safeguarding the integrity and culture of our nation while upholding the prevailing customary rules. Thus, we can ensure the preservation of the Baduy tribe's culture while maintaining a harmonious balance with nature and their traditions.